Designing E-comic for English Reading Material for Grade Eight in Tanjungpinang - Zakiyah Ramadhani; Dewi Nopita; Rona Elfiza (Universitas Maritim Raja Ali Haji (UMRAH), 2022)
The research aimed to design an e-comic for English Reading Material for online learning at grade eight of SMPN 11 Tanjungpinang. The design of e-comic for English reading material can be considered to make the students interested and motivated in learning English during online environment. This research focused on designing English reading material about recount text for grade eight. The research design was R&D based on ADDE by Richey and Klein consisted of analyze, design, develop, and evaluation. The subject of this research was the 8.4 class students which consisted of 25 students. The instruments were interview and questionnaires. The researcher was analyzed the data by using qualitative and quantitative techniques. The results of the research showed that the practicality of e-comic was very high (91.5%). It can be concluded that the e-comic for English reading material was interested, motivated, and contextualized to learn by the students at SMPN 11 Tanjungpinang.